Resíduos de agrotóxicos em água potável usando SPE e determinação rápida por LC-MS/MS e GC-MS/MS - Donato, Filipe Fagan (2012)
The use of pesticides always has been associated with the effective control of pests or invasive weeds to ensure an increase in the food production. However, the indiscriminate use of these substances has caused the degradation of water resources. In Brazil, the Ministry of Health through Ordinance 2914 defines several parameters of potability, among them, the maximum limits allowed for same pesticides. In this work it was developed and validated a method for the determination of residues of 70 pesticides in drinking water using (SPE) for sample preparation and determination by Gas and Liquid Chromatography coupled to tandem mass spectrometry, triple quadrupole analyzer (GC-(TQ)MS/MS and LC- (TQ)MS/MS). It was evaluated different sample volume, sorbents and solvent of elution. The best results were obtained using 100 mL sample acidified at pH 2.5, Oasis® SPE cartridge HLB 60 mg/3 mL and dichloromethane/methanol as eluent. Analytical curves were linear between 10 and 250 Sg L-1, with r2 values greater than 0.99 for all compounds. The values of method LOQ were 0.02 Sg L-1 for aldrin, dieldrin and chlordane and 0.5 Sg L-1 for the other compounds. To evaluate accuracy the blank samples ware fortified at 0.5, 1.5 and 4.0 Sg L- 1 and an extra level at 0.02 Sg L-1 for aldrin, dieldrin and chlordane. The method showed good precision, with RSD values below to 20% and good accuracy, with recoveries between 70 and 120%. Only the compounds methamidophos, aldicarb, benfuracarb, terbufos, benomyl and thiophanate methyl were not recovered adequately. The matrix effect was evaluated, showing upper 10% for the most compounds. In order to compensate this effect, analytical curves were obtained with standarts prepared in blank extracts of the matrix. The validated method was applied to 12 samples of drinking water of different characteristics (river, shed, well and treated water), and just one of the river samples presented residues of lambda-cyhalothrin. The results indicate that the proposed method is suitable for analysis of pesticides residues in drinking water, since all the validation parameters met the suggested limits and parameters for validation of chromatographic methods.